Comparison of the effects of three kinds of hand exercises on improving limb function in patients after transradial cardiac catheterization - Xinyue Zhang; Zhipeng Bao; Lan Wei; Zairan Zhang; Yanli Hu; Dandan Xu; Wei Sun; Dongmei Xu (Elsevier, 2023)
Objectives: This study aimed to compare effects of different hand exercises on improving limb function in patients after transradial cardiac catheterization. Methods: This single-center, randomized clinical trial was conducted from August 20, 2020, to July 20, 2021, at an academic medical center. A total of 102 participants were selected from a Class A tertiary hospital in Nanjing, China and randomized into three groups: finger exercise group (n = 34), acupoint massage group (n = 34), and handgrip exercise group (n = 34). Symptoms of edema and pain were defined as primary outcomes, while skin temperature and degree of bleeding as secondary outcomes, which were monitored and measured 1, 2, and 4 h, after the intervention. Results: Among the 99 participants who completed the process, the palm edema was gradually relieved in the handgrip exercise group at 2 h (H = 6.710, P = 0.035) and 4 h (H = 10.060, P < 0.001) following the intervention. The edema of fingers in the handgrip exercise group was obviously relieved at 2 h (H = 9.353, P < 0.01) and 4 h (H = 10.699, P < 0.001) following the intervention compared with the other two groups. In addition, the pain score at 4 h (H = 7.048, P = 0.029) was clearly decreased in the handgrip exercise group. However, there was no significant difference in the punctured limb's skin temperature (H = 0.922, P = 0.631) and the degree of bleeding (H = 0.123, P = 0.940) among the three groups. Conclusions: We found that handgrip exercise is more effective in reducing the edema of the limbs than finger exercise and acupoint massage.